Terlipressin Improves Renal Function and Reverses Hepatorenal Syndrome in Patients With Systemic Inflammatory Response Syndrome - Wong, Florence; Pappas, Stephen Chris; Boyer, Thomas D.; Sanyal, Arun J.; Bajaj, Jasmohan S.; Escalante, Shannon; Jamil, Khurram (Clinical gastroenterology and hepatology, 2017)
Patients with systemic inflammatory response syndrome (SIRS) along with decompensated cirrhosis and renal dysfunction have a poor prognosis and a lower response to treatment. We evaluated the effect of SIRS on the response of hepatorenal syndrome type 1 (HRS-1) to terlipressin. We performed a retrospective study of data from a trial of the effects of terlipressin (1 mg every 6 hours or placebo with concomitant albumin) in 198 patients with HRS-1, performed at 50 investigational sites in the United States and 2 in Canada from October 2010 through February 2013. We identified patients with 2 or more criteria for SIRS, without untreated infections (28 received terlipressin and 30 received placebo), and patients with less than 2 criteria for SIRS (control subjects). Primary endpoints included HRS reversal (a decrease in serum level of creatinine to ≤1.5 mg/dL), confirmed HRS reversal (defined as 2 serum creatinine levels ≤1.5 mg/dL, ≥ 48 hours apart), and survival for 90 days after treatment. Baseline characteristics were similar between groups, apart from slightly higher white blood cell counts and heart rates, and slightly lower serum levels of bicarbonate in patients with SIRS versus without SIRS. HRS was reversed in 42.9% of patients who received terlipressin with SIRS (12/28) versus 6.7% of patients who received placebo (2/30) (P = .0018); confirmed HRS reversal occurred in 32.1% of patients who received terlipressin with SIRS (9/28) versus 3.3% who received placebo (1/30) (P = .0048). A larger proportion of patients with SIRS who received terlipressin survived for 90 days without a transplant (13/28; 46.4%) than patients with SIRS who received placebo (7/30; 23.3%) (P = .076). In an analysis of data from a placebo-controlled study, we found that terlipressin improved renal function and reversed HRS in a higher proportion of patients with HRS-1 and SIRS than patients who received albumin plus placebo. ClincialTrials.gov, number NCT 01143246.